Development of Educative Magazine as a Bilingual Learning Medium Based on Arabic and English Vocabulary - Luthfi Farihatun Nisa'; Nurul Murtadho (Universitas Islam Negeri Palangka Raya, 2023)
The utilization of bilingual learning media based on educative magazines has been widely found in various educational practices today. However, its existence is still limited to being used in the field of science, even though the essence of the magazine as a mass communication medium is very close to its role in the language field. Therefore, this study aims to develop an educative magazine-based bilingual learning medium to improve Arabic and English vocabulary skills. This development research using Dick & Carey's 1950 ADDIE model focuses on media development, so this research maximizes the process of analysis, design, development, and formative evaluation stages at each stage. Sources of research data are primary and secondary data obtained by interview techniques, literature studies, and expert test questionnaires. The data collected was then analyzed by using the interrater-agreement model technique to find a validity index. The research results based on language and material expert tests show an index of 1.0 with revisions. In contrast, the research results based on media expert tests show an index of 0.85 with revisions. Thus, it shows that this medium is very easy, precise, interesting, and suitable for future application in the bilingual learning process, which aims to understand and improve bilingual vocabulary.